Pollen morphology of some Arenaria taxa (Caryophyllaceae) - Doğan, Cahi̇t; Erdem, Sedat Ömer (Phytotaxa, 2018)
Palynological characteristics of 11 taxa belonging to the genus Arenaria (Caryophyllaceae) have been examined. Pollen grains in the pollen slides, which were prepared according to the method of acetolysis, morphological features were determined with light microscope and also with SEM, then microphotographs of pollens were taken. Morphological examinations were performed on the part of the work carried out with light microscope, pollen sizes, pore sizes and numbers were observed to vary between taxa. The pollen type of the studied taxa is pantoporate (periporate), pollen shape is prolate spheroidal, exine structure is subtectate, the ornamentation is microechinate-perforate. The pores are covered with operculum and the surface of the operculum is microechinate. According to the results of the study, pollen definitions of the taxa were made. Based on different palyno-morphological characters, a taxonomic key was develop for quick and accurate identification. The results of the study corroborate that morphological features, such as axes, aperture number, Plg, and Plt diameter and distance between pores, show differences which can be taken into consideration in the systematic discrimination within the groups, and also for discrimination of the taxa in the genus Arenaria.